Հայկական հարցը և Հայոց եկեղեցին 1877-1878 թթ. - Միքայել Մինասյան (ՀՀ ԳԱՍ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
Русско-турецкая война 1877-1878 гг. побудила все слои армянского общества выступить за осуществление преобразований в Турецкой Армении на уровне славян Балканского полуострова. На политическом и дипломатическом поприще активность проявило руководство Армянской церкви. Russian-Turkish war in 1877-1878 induced all sections of Armenian society to stand for transformation in Turkish Armenia on the level of Slavs of Balkan peninsula. In political and diplomatic fields the leadership of Armenian Church showed its activity.
Keywords: Քրիստոնեություն; Հայկական հարց